Counselling to promote physical activity - Hardcastle, Sarah; Taylor, A. (Routledge, 2014)
Despite the compelling evidence of the health benefits of being physically active, few people are sufficiently active to benefit their health and there is a need to focus on effective interventions to increase motivation for continued physical activity participation. Counselling interventions, such as motivational interviewing show promise in facilitating lifestyle behavioural changes through the promotion of autonomous motives for change. This chapter summarises the key principles and strategies used in motivational interviewing and outlines what exercise professionals can do to increase the likelihood that counselling will promote behaviour change. Based on the underlying principles of motivational interviewing and the strategies employed, there is real promise that motivational interviewing interventions are likely to promote long-lasting, sustained behaviour change. This is because of its central emphasis on eliciting personal motives for change, working through ambivalence, building confidence and promoting more autonomous forms of motivation.